Human Consciousness: Psychic and Energetic Approach - Varii, Myron Y. (Journal of Intellectual Disability - Diagnosis and Treatment, 2020)
Objective: The article researches the essence and bases of functioning and development of the consciousness (conscious level of the human psyche) in the context of the psychic and energetic conception of the psyche and psychic. Background: There are thousands of writings about consciousness. However, operational and functional processes of conscious perception of the world and self, understanding of various connections in this world, determining of attitude to it and self and forming responsibilities for results of interaction are described unclearly almost in all psychological conceptions. Method: To disclose the human consciousness, the following methods were used: analysis, synthesis, comparison, abstraction, generalisation and grouping of existing knowledge about a human, functioning of the human psyche. Results: It has been proved that the conscious is the plurality of different psychic, about which human is aware. We have found out that the personal unconscious contains phenomena that are in the subconscious, not in the unconscious because "came" from consciousness. Conclusion: This plurality is the basis of forming psy-programs of different degree of complication and perfection to transform the world as external psyche through activity, behaviour, their comparison with previous experience, isolation of "Self" from the environment to analyse it and consciousness from different perspectives.